2016
DOI: 10.1371/journal.pone.0155789
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Continuity between Primary Care and Surgical Care in Colon Cancer

Abstract: BackgroundImproving continuity between primary care and cancer care is critical for improving cancer outcomes and curbing cancer costs. A dimension of continuity, we investigated how regularly patients receive their primary care and surgical care for colon cancer from the same hospital and whether this affects mortality and costs.MethodsUsing Surveillance, Epidemiology, and End Results Program Registry (SEER)-Medicare data, we performed a retrospective cohort study of stage I-III colon cancer patients diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…Since PCPs do not order MRIs, it is not immediately clear why a physician network with more PCPs would have a slower adoption of MRI. A previous study has shown an association of the co‐localization of surgical care and PCPs at the same hospital with significantly lower costs of care in colon cancer, suggesting that PCP peer relationships and placement in care structures may impact resource utilization in cancer care . However, evidence on the relationship between PCP concentration and spending is mixed.…”
Section: Discussionmentioning
confidence: 99%
“…Since PCPs do not order MRIs, it is not immediately clear why a physician network with more PCPs would have a slower adoption of MRI. A previous study has shown an association of the co‐localization of surgical care and PCPs at the same hospital with significantly lower costs of care in colon cancer, suggesting that PCP peer relationships and placement in care structures may impact resource utilization in cancer care . However, evidence on the relationship between PCP concentration and spending is mixed.…”
Section: Discussionmentioning
confidence: 99%
“…A ZIP code-level variable was included instead, and it was shown to be a confounder and improved the model fit, a method that previous cancer studies have done. 45,46 Despite these limitations, this study is innovative because we used a population-based data source (i.e., generalizable across the entire state) of adults who received a colonoscopy and had the power to detect subgroup differences across race/ethnicity, insurance status, and patient county of residence.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown benefits related to continuity of care with improvements in survival and decreases in rehospitalization and health care resource use (12)(13)(14)(15)(16)(17)(18)(19)(20). These studies have primarily demonstrated the benefits of continuity of care throughout outpatient medical visits (18,19), after hospitalization (defined as being seen by a familiar physician after hospital discharge or providing outpatient physicians with information about the hospitalization) (14)(15)(16)(17), and having continuity between surgical and primary care providers (20). Our study extends these findings, focusing on a very high-risk population with high mortality during rehospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Discontinuity of care has been shown to be common in both complex surgical and nonsurgical patients (11)(12)(13). Continuity of care (defined in various ways) is associated with improvements in survival as well as with decreased rates of rehospitalization, acute care use, and costs (12)(13)(14)(15)(16)(17)(18)(19)(20). Critically ill patients, particularly those receiving mechanical ventilation, are a group of medically complex patients at high risk for rehospitalization and thus represent an important population in which to determine whether a lack of continuity of care adversely affects outcomes of rehospitalization.…”
mentioning
confidence: 99%